2015
DOI: 10.4236/ojn.2015.57064
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Chronic Obstructive Pulmonary Disease Computer Game as a Learning Tool for Nursing Students

Abstract: Simulation games that are close to actual clinical situations can assist students in the learning process and, through the active presentation of subject material, help them acquire necessary knowledge. The aims of this study were to develop a computer game focused on caring for patients with chronic obstructive pulmonary disease (COPD) in the outpatient clinic and to evaluate the nursing students' change in knowledge and their satisfaction score after they played this computer game. This study had a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A study on nursing students showed that the game-based virtual reality application significantly improved advanced life support [ 42 ]. Tsai et al assessed the effectiveness of computer games for increasing nurses’ understanding of chronic obstructive pulmonary disease, finding that their COPD care knowledge scores significantly improved after playing the game [ 27 ]. However, game-based virtual reality applications have proven valuable in teaching psychomotor skills and enhance the visual clinical environment, such as personal protective equipment and sharps safety, which are too tough to understand through a single observation in the traditionally-lab class.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study on nursing students showed that the game-based virtual reality application significantly improved advanced life support [ 42 ]. Tsai et al assessed the effectiveness of computer games for increasing nurses’ understanding of chronic obstructive pulmonary disease, finding that their COPD care knowledge scores significantly improved after playing the game [ 27 ]. However, game-based virtual reality applications have proven valuable in teaching psychomotor skills and enhance the visual clinical environment, such as personal protective equipment and sharps safety, which are too tough to understand through a single observation in the traditionally-lab class.…”
Section: Discussionmentioning
confidence: 99%
“…after playing the game [27]. However, game-based virtual reality applications have proven valuable in teaching psychomotor skills and enhance the visual clinical environment, such as personal protective equipment and sharps safety, which are too tough to understand through a single observation in the traditionally-lab class.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations